Sweet whey protein addition to a low-fat yogurt - L´ópez-Calvo, Rebeca (2021)
Introduction. Bovine milk whey is a source of nutrients, so its use would benefit the consumer and help reduce the environmental impact of discarding it. In Costa Rica, most of it is destined as animal feed or disposed in rivers and soils. It is necessary to develop sustainable alternatives for its use. Objective. To evaluate the effect of serum protein incorporation on the physical characteristics, amino acid content, and storage behavior of yogurt with whey protein. Materials and methods. The study was developed at the facilities of the Universidad de Costa Rica, during 2011-2015. The whey was acidified to a pH of 4.8, heated to 90 ºC and kept at rest for 90 min to achieve protein precipitation. Two samples of low-fat whipped yogurt were developed, one control and one with protein extracted from sweet whey. Viscosity, syneresis, pH, macronutrient, total and free amino acids were determined for both yogurts. The behavior of the yogurt with added protein and the overall palatability were evaluated during twenty-four days of storage were evaluated by sensory analysis. Results. A yogurt with added protein showed no significant differences, in comparison with control yogurt, for pH, syneresis, macronutrients, free amino acids, total amino acids (with exception for threonine), syneresis – storage time interaction and general pleasantness during storage. Conclusion. The nutritional quality and functionality of yogurt with added protein was maintained with respect to the control, which would allow the incorporation of whey protein with a feasible methodology on an artisanal scale.